Surgery in nontuberculous mycobacteria pulmonary disease. Issue 4 (December 2018) - Lu, Mimi; Fitzgerald, Dominic; Karpelowsky, Jonathan; Selvadurai, Hiran; Pandit, Chetan; Robinson, Paul; Marais, Ben J.
Medical treatment of pulmonary nontuberculous mycobacteria (NTM) disease has highly variable outcomes. Despite the use of multiple antibiotics, sputum clearance is often difficult to achieve, especially in cases with macrolide resistant NTM infection. Immunocompromised patients and those with structural lung disease are at increased risk, although occurrence in immunocompetent patients without structural lung disease is well recognised. Most pulmonary NTM disease involves Mycobacterium avium complex (MAC), but with enhanced identification multiple species have now been recognised as opportunistic pathogens. The observed increase in NTM disease, especially infection with multidrug-resistant Mycobacterium abscessus complex, is probably multifactorial. Surgery has been used as adjuvant treatment in patients with 1) focal disease that can be removed or 2) bothersome symptoms despite medical treatment that can be ameliorated. Early post-surgical mortality is low, but long-term morbidity and mortality are highly dependent on the degree of lung involvement and the residual lung function, the potency of medical treatment and the type of surgical intervention. In conjunction with antibiotic therapy, reported post-surgical sputum clearance was excellent, although publication bias should be considered. Bronchopleural fistulae were problematic, especially in pneumonectomy cases. Study results support the use of minimal resection surgery, in a carefully selected subgroup of patients with focal disease or persistent symptoms. Educational aims: To critically review the literature describing the use of surgery in the treatment of pulmonary disease caused by nontuberculous mycobacteria (NTM). To assess the outcomes and complications observed with different surgical approaches used in the treatment of pulmonary NTM disease. Minimal resection surgery, in a carefully selected subgroup of patients with focal disease or persistent symptoms can be considered as an adjuvant therapy in the treatment of pulmonary nontuberculous mycobacterium infection. http://ow.ly/ONSC30mesFC